Development and characterization of arrowroot (Maranta arundinacea L.) fibre-reinforced thermoplastic starch biocomposites - Jamal, Tarique (2022)
Petroleum-based plastics are one of the most commonly used materials in the packaging industry, which has been a source of concern for the global environment. The increased production of harmful environmental plastic waste has fueled the development of natural-based, renewable, and biodegradable materials. Therefore, environmental sustainability and the absence of harmful carbon emissions during and after processing are desirable characteristics of potential materials. Furthermore, the widespread acceptance of natural fibres and biopolymers as green materials is being driven by the rapid depletion of petroleum resources, as well as a growing awareness of global environmental issues associated with the use of conventional plastics. Also, rising petrochemical prices and environmental concerns are driving the development of natural polymeric materials for a wide range of applications in food-packaging materials that are more consumer-friendly. Among these materials, arrowroot (Maranta arundinacea L.) has emerged as a vital and effective source of starch and fibres. Arrowroot belongs to the Marantaceae family, which is typically found in tropical forests. When compared to other agro-based products, arrowroot starch and fibres has some distinct advantages, including lower cost than other natural sources and greater accessibility. Therefore, several laboratory experiments were conducted to produce and characterize arrowroot fibres, biopolymers, and biocomposite films. The samples were developed using a solution casting method. Initially, arrowroot bagasse (ABF) and husk fibres (AHF) were extracted and the physical, chemical, thermal, morphological properties, as well as crystallinity, were characterized. The chemical composition analysis revealed that ABF has higher cellulose (45.97 %) than AHF (37.35 %), cassava bagasse (10.04 %), and corn hull (15.30 %). In addition, ABF is significantly low in lignin (2.78 %) and density (1.11 g/cm3 ) than AHF, corn hull, and cassava. Concerning the above characterization of fibres, it was found that the lignocellulosic biomasses from arrowroot are alternative promising sustainable material, which can be used in food packaging as a renewable filler. The second stage was designed to investigate the development of arrowroot starch (AS) films using glycerol (G) as a plasticizer at the ratio of 15, 30, and 45% (w/w, starch basis) to achieve a new biopolymer for the application of environmentally friendly materials. The developed films were analysed in terms of physical, structural, mechanical, thermal, environmental, and barrier properties. The incorporation of glycerol into AS film-making solution reduced the brittleness and fragility of films. An increment in glycerol concentration caused an increment in film thickness, moisture content, and solubility in water, whereas density and water absorption were reduced. The tensile strength and modulus of G-plasticized AS films were reduced significantly from 9.34 to 1.95 MPa and 620.79 to 36.08 MPa, respectively, while elongation at break was enhanced from 2.41 to 57.33 %. FTIR analysis revealed that intermolecular hydrogen bonding occurred between glycerol and AS in plasticized films compared to control films. The G-plasticized films showed higher thermal stability than control films. Water vapour permeability (WVP) of plasticized films increased by an increase in glycerol concentrations. Furthermore, a novel biodegradable thermoplastic arrowroot starch (TPAS) film containing arrowroot fibre (AF) at different concentrations (0, 2, 4, 6, 8, and 10 wt.%) was developed and characterized in terms of thermal, antibacterial activity, water vapor permeability (WVP), biodegradability, physical, morphological (FESEM), tensile and tear strength, and light transmittance properties. The TPAS/AF biocomposite film revealed a higher degradation temperature (313.02 ℃) than other biocomposite films, indicating better thermal stability. Furthermore, increasing AF concentration led to a significant (p < 0.05) reduction in the linear burning rate and WVP of the biocomposite films from 248.9 to 115.2 mm/min and 8.18 ×10-10 × g. s-1.m-1. Pa-1 to 5.20 ×10-10 × g. s-1.m-1. Pa-1, respectively. The tensile and tear strengths of TPAS/AF composites were increased significantly from 2.42 to 15.22 MPa and 0.83 to 1.28 MPa, respectively, and the elongation was decreased from 46.62 to 6.21%. The findings revealed that after being reinforced with fibres, the mechanical properties enhanced, and the optimum filler content was 10%. Regardless of fibre loadings, the results of water absorption testing revealed that the composite films immersed in seawater and rainwater absorbed more water than distilled water. In addition, the incorporation of AF and control film showed an insignificant effect against three pathogenic bacteria including Staphylococcus aureus (ATCC 43300), Escherichia coli (ATCC 25922), and Bacillus subtilis (B29). The soil burial findings demonstrated that the weight loss of TPAS/AF biocomposite films was significantly higher than TPAS film. Overall, the reinforcement of arrowroot fibre with TPAS film improves the properties of biocomposites for environmentally friendly food packaging applications. The development of fully biodegradable packaging films is essential in the continuous effort to address current environmental issues and gradually replace commonly used conventional packaging materials.